EAFIA Interior Design / Erina Izzati Aneesa A. Tahir ... [et al.] - A. Tahir, Erina Izzati Aneesa; Diman, Adzura; Hamdan, Farah Erlinda; Farman, Ili Nabihan; Idris, Adiza (2012)
Our business name is EAFIA Interior Design and we provide a service designing your interior home and office. Our business location is at Lot No. 148, Alamesra Plaza Permai, Sulaman Coastal Highway, 88400 Kota Kinabalu, Sabah. We form a partnership business for this interior design service and have a task and responsibility on their own position whereby General Manager is Erina Izzati Aneesa A.Tahir, Administration Manager is Adzura Binti Diman, Marketing Manager is Farah Erlinda Binti Hamdan, Operational Manager is Adiza Binti Idris, and Financial Manager is Ili Nabihan Binti Farman. Each of this position was very important to ensure the business objective, vision and mission can be achieved. In this partnership business we already make an agreement which is agreed by every member and this agreement is to prevent from any problem occur in the future. Apart from that, we also have an incentive scheme for employee to encourage them to more responsible and have a high commitment in carrying their job. We had given incentive scheme like salary, employee's provident fund (EPF), Social Security Organization (SOCSO), emergency leave, bonus, insurance and maternity leave. Other than that, we also have contribution among our members in term of cash, office equipment and fixed assets. Our cash contribution is RM50, 000. We purposely chose our business name 'EAFIA', because we want our customer to feel comfortable with by knowing our names. They also can trust us designing their home into becoming their own dream home. EAFIA stands for our names that is E-Erina. A-Adzura, F-Farah, A-Adiza, and l-lli. The idea came up with this interior designing idea was originated came from Erina and Farah as both of them are familiar with this kind of business. We chose our location of business in Alamesra because, nowadays is a strategic area to open a business due to the rapid development around that area. This is also due to the many new construction of housing area in Sepanggar, and in Alamesra itself. The shop we have selected can be easily seen from the main road which is an advantage for our business to be known. There are also plenty of amenities in this area for the benefit of our business and our customers.